Correlation of the tutor's knowledge and social class with feline obesity (Research, Society and Development, 2023)
As well as the relationship between parental lifestyle and human childhood obesity, it has already been proven that in dogs, the lifestyle of tutors predisposes to weight gain. Therefore, it is important to determine whether different characteristics of cat owners influence body condition. The aim of this study was to evaluate the correlation between feline body score, knowledge of food management and social class of their tutors. The data were obtained through a questionnaire applied to the tutors and predetermined photos of the animals evaluated by the same researcher in order to classify them in the modified scale of Body Condition Score. There was a positive correlation between the felines' score with the type of feed provided and the income of their guardians, there was also a positive correlation between the tutor's knowledge and their social structure. Therefore, it can be stated that knowledge, education and income have an impact on several factors that influence the development of feline obesity.